Increasing Students' Understanding in Learning Hadith with the Direct Instruction Model in Class VII E MTs Walisongo Ngabar Putri - Hanny Faridhotul Mukarromah; Imam Rohani (Universitas Muhammadiyah Semarang, 2023)
This study aims to determine how effective the direct instruction model is in improving the understanding of VII E grade students of MTs Wali Songo Ngabar Putri in Hadith subjects through the application of the direct instruction method or direct instruction method. The research subjects were class VII E MTs Wali Songo Putri Ngabar, totaling 24 female students.. This research is a classroom action research method (CAR) which consists of two cycles with the design of each cycle consisting of four stages, namely the first stage is planning, the second stage is acting (implementing), observing and the third stage is reflecting. Research data is obtained during action research until the final assessment of the action. The results showed that the results of the initial test after the action in the first cycle of 24 students there were 13 students (54.17%) declared complete, while for the other 11 students (45.83%) were declared incomplete. In the second cycle the number of students who completed as many as 20 students (83.3%), while the other 4 students had not completed (16.7%). Thus, it can be proven that the application of the direct instruction model in Hadith subjects for class VII E MTs Wali Songo Ngabar Putri about sneezing etiquette and yawning manners have a positive impact on increasing student understanding.